Optimasi Jadwal Pelajaran Berbasis Integer Linear Programming di MTS Nurul Islam Bumiharjo Jepara - Rokhim, Mansyur; Saputro, Heru (Scimadly Publishing, 2025)
Various limitations such as teacher availability, classroom space, lesson time, and subject load. At MTs. Nurul Islam Bumiharjo, the schedule preparation process is still done manually, which often causes schedule conflicts and suboptimal use of resources. This study aims to optimize the preparation of lesson schedules by applying the Integer Linear Programming (ILP) method, one of the techniques in operations research that is able to handle scheduling problems with many constraints. The ILP model is designed to minimize overlapping teacher and room schedules, and to ensure the distribution of lesson hours according to curriculum standards. The primary data used is the 2024/2025 school year lesson schedule. The results of the study show that the ILP model is able to produce a more efficient and less conflicting schedule solution than the manual method. Thus, this approach can be a strategic alternative in a data-based school scheduling system.